2002
DOI: 10.1080/09629350220131926
|View full text |Cite
|
Sign up to set email alerts
|

Role of histamine in the inhibitory effects of phycocyanin in experimental models of allergic inflammatory response

Abstract: It has recently been reported that phycocyanin, a biliprotein found in the blue-green microalgae Spirulina, exerts anti-inflammatory effects in some animal models of inflammation. Taking into account these findings, we decided to elucidate whether phycocyanin might exert also inhibitory effects in the induced allergic inflammatory response and on histamine release from isolated rat mast cells. In in vivo experiments, phycocyanin (100, 200 and 300mg/kg post-orally (p.o.)) was administered 1 h before the challen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(35 citation statements)
references
References 24 publications
0
34
0
Order By: Relevance
“…C-Pc, has significant antioxidant and radical scavenging properties [7,8], it inhibits mouse ear inflammation [9], prevents acetic acid induced rat colitis [10] and has anti-arthritic properties [11]. It also inhibits COX-2 [12,13], inflammatory allergic reactions [14], prostaglandins, leukotrienes [15] and TNF-alpha production [16].These actions are expected to improve EAE induced animals, mainly because Sp/C-Pc have been shown to restore the organic and functional neuronal damage linked to senility [17] and neurodegenerative disorders [18][19][20]. However, here we demonstrate an additional and probably more fundamental property of C-Pc, its ability to trigger Treg subset induction.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%
“…C-Pc, has significant antioxidant and radical scavenging properties [7,8], it inhibits mouse ear inflammation [9], prevents acetic acid induced rat colitis [10] and has anti-arthritic properties [11]. It also inhibits COX-2 [12,13], inflammatory allergic reactions [14], prostaglandins, leukotrienes [15] and TNF-alpha production [16].These actions are expected to improve EAE induced animals, mainly because Sp/C-Pc have been shown to restore the organic and functional neuronal damage linked to senility [17] and neurodegenerative disorders [18][19][20]. However, here we demonstrate an additional and probably more fundamental property of C-Pc, its ability to trigger Treg subset induction.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%
“…Remirez et al (23) reported that in rats phycocyanin prevents allergic dermatitis by inhibiting the release of histamine caused by compound 48/80, a histamine releaser. Romay et al (24) also reported that phycocya nin administration before application of arachidonic acid prevents the inflammatory edema in the ears of mice, reduces the production of prostaglandin E2 and leukotriene B4, and also inhibits the activity of cycloox ygenase, an enzyme that synthesizes prostaglandins …”
mentioning
confidence: 99%
“…These are linked−but not restricted− to their conventional anti-oxidant, free radical scavenging and anti-infl ammatory properties [9][10][11][12], such as the selective COX-2 enzyme inhibition [13,14], but also to the modulation of the expression of several genes linked to other biological processes [15]. In the anterior cerebral cortex of rats subjected to a global acute brain hypoperfusion, we have observed that a total of 93 genes were upregulated and 97 genes were down-regulated due to the therapeutic treatment of PCB.…”
Section: C-phycocyanin and Phycocyanobilin As Possible Cytoprotectivementioning
confidence: 99%